Design and Implementation of Low-Complexity Pre-Equalizer for 1.5 GHz VLC System - Runxin Zhang; Jian Xiong; Menghan Li; Lu Lu (IEEE Photonics Journal, 2024)
Visible light communications (VLC) has experienced rapid development in recent years as a strong competitor for next-generation wireless applications due to its wider bandwidth, higher security, and better electromagnetic immunity compared with conventional radio frequency (RF) microwaves. Although state-of- the-art VLC systems can achieve Gbps data rates by employing equalization schemes, designing a general low-complexity VLC transmitter with hundreds of MHz 3-dB bandwidth is still challenging due to the narrow modulation bandwidth nature of light emitting diodes (LEDs). In this paper, we first present a second-order equivalent circuit model for the LED, based on which we propose a general second-order equalizer (GSE) with low complexities, consisting of less than 5 passive capacitors, inductors, and resistors. We show that the GSE can enlarge the LED transmitter's bandwidth to a few hundred MHz. To validate our GSE, we build a broadband VLC transmitter using commercial-off-the-shelf (COTS) red, green and blue (RGB) LEDs, whose bandwidth is 14 MHz, by summing up three colours. Experimental results show that our proposed GSE can extend the transmitter's 3-dB bandwidth from 14 MHz to 1.5 GHz. Furthermore, we demonstrate that a VLC system utilizing the proposed GSE transmitter can achieve 1.15 Gbps data rates at a distance of 250 cm with a bit error ratios (BERs) below the forward error correction (FEC) limit $3.8 × 10^{-3}$ .